Evaluasi Kurikulum Pembelajaran Pendidikan Agama Islam: Evaluation of Islamic Religious Education Learning Curriculum - Jaya Kesuma, Muhammad Ilham; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (STAI Publisistik Thawalib Jakarta, 2024)
The education curriculum must evolve to meet contemporary demands, fostering a competent and innovative generation. Evaluating the Islamic Education curriculum is essential for improving understanding and practice of religious teachings. This research aims to analyze the Islamic Education curriculum evaluation process at Public Senior High School 5 Bandar Lampung, utilizing a qualitative case study method. Data is gathered through interviews, observations, and documentation, with processing involving condensation, presentation, and drawing conclusions. Validity is ensured through triangulation of sources and methods. Findings indicate that planning for Islamic Education curriculum evaluation involves setting goals, achievement indicators, and relevant assessments. The school assesses student needs and adapts materials to the local context. However, conventional teaching methods and low student participation are prevalent, highlighting challenges in aligning materials with modern needs and gaps between curriculum objectives and practice. To enhance effectiveness, project-based methods and group discussions should be implemented, alongside teacher training in educational technology, ensuring the curriculum remains relevant to contemporary challenges.